Conflict and coexistence proceedings of the 29th Congress of the Union Euopéenne des Arabisants et Islamisants, Münster 2018 - Springberg, Monika 1963-; Bauer, Thomas 1961- (Orientalia Lovaniensia analecta, 2022)
This volume comprises nineteen papers presented at the 29th Congress of the Union Européenne des Arabisants et Islamisants at the University of Münster, Germany in September 2018. The articles focus on a variety of phenomena from premodern and modern Islamicate cultures and societies. They are organized in sections on Sciences, Literature and Linguistics, Islamic Law, Theology and Philosophy, History and Society and Material Culture. The variety of approaches to the sources and methods employed represents the width of European research in this field. Thus, the volume provides an easy access to the newest European scholarship on the Islamicate Near and Middle East.